2017
DOI: 10.14379/iodp.proc.357.104.2017
|View full text |Cite
|
Sign up to set email alerts
|

Central sites

Abstract: Operations 3 Lithology, alteration, and structure 20 Bulk rock geochemistry 21 Fluid chemistry 21 Microbiology 23 Sensor package data 29 Borehole plugs 31 Physical properties 35 Downhole logging 36 Paleomagnetism 38

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…The mafic intrusions in these cores have pale brown to pinkish-brown central domains that are surrounded by external dark green domains made up mostly of chlorite (chlorite blackwall), which in turn grade into talc-amphibole-rich domains at the contact to the serpentinites. The pinkish brown domains were originally described as rodingites (Früh-Green et al, 2017d), which have been found during previous sampling campaigns along the southern wall of the Atlantis Massif (Boschi et al, 2006a). However, subsequent analyses have yet to identify typical Ca-Al silicates, such as epidote (clinozoisite), diopside, prehnite, (hydro)garnet or vesuvianite, which are commonly found in rodingites in similar associations with serpentinites.…”
Section: Serpentinization and Metasomatismmentioning
confidence: 99%
“…The mafic intrusions in these cores have pale brown to pinkish-brown central domains that are surrounded by external dark green domains made up mostly of chlorite (chlorite blackwall), which in turn grade into talc-amphibole-rich domains at the contact to the serpentinites. The pinkish brown domains were originally described as rodingites (Früh-Green et al, 2017d), which have been found during previous sampling campaigns along the southern wall of the Atlantis Massif (Boschi et al, 2006a). However, subsequent analyses have yet to identify typical Ca-Al silicates, such as epidote (clinozoisite), diopside, prehnite, (hydro)garnet or vesuvianite, which are commonly found in rodingites in similar associations with serpentinites.…”
Section: Serpentinization and Metasomatismmentioning
confidence: 99%
“…REE patterns group by lithology ( Figure F20; see Figure F23 in the Central sites chapter [Früh-Green et al, 2017a] and Figure F11 in the Western sites chapter [Früh-Green et al, 2017d]). Serpentinized ultramafic rocks have relatively flat to slightly light rare earth element (LREE) depleted chondrite-normalized patterns (typically centered around 1 or below).…”
Section: Summary Of All Sitesmentioning
confidence: 99%
“…S13-S14). Although core samples from Site M0076 tended to be coherent, they were often rich in veins (Früh-Green et al, 2017b), which likely allowed transfer of PFC into the interiors of some samples (Supplement Figs. S15-S16).…”
Section: Assessment Of Sample Quality For Deep Biosphere Investigationsmentioning
confidence: 99%